Smoking and Its Consequences in Pregnant Women in Ukraine - Andreeva, Tatiana I. (World Bank, Washington, DC, 2013)
Smoking during pregnancy increases the risk of a number of complications of pregnancy and can have adverse effects on the child. This study provides data from Ukraine that are consistent with the international literature on the effects of smoking during pregnancy. The study of nearly 700 women in Ukraine examined the rate of smoking during pregnancy and factors related to continued smoking. It documents the outcomes of pregnancy in women who smoked prior to pregnancy, and who smoked during pregnancy compared to those who did not. It also looks at pregnancy outcomes with respect to the baby's father smoking. Smoking during pregnancy is at low levels in Ukraine (less than 5 percent of pregnant women), but is associated with family structure, the baby's father smoking, and the number of previous abortions. It is also associated with placental insufficiency, low birth weight, fetus hypotrophy, and hip joint dysphasia. The father's smoking is associated with decreased fertility, late toxicosis, miscarriage threat in third trimester, small baby, and lower infant functional status. There was no evidence that information on the dangers of smoking while pregnant encouraged cessation.